Effect of Compost Addition on Porosity and Hydraulic Properties of Different Textured Soils - Nurten İşler; Yasemin Kavdır (Journal of Advanced Research in Natural and Applied Sciences)
This research aimed to investigate the temporal variations in soils of three distinct textures that were amended with composts derived from olive pomace (OPC) and vineyard pruning waste (VPC). The compost was prepared in reactors with automatic temperature and aeration control. This research encompasses three distinct soil textures, five varying compost applications, and ten separate sampling intervals following the compost application and replicated four times. After 210 days of incubation, 6% VPC application increased the field capacity value by 27.7% compared to the control, especially in sandy loam soil. At the same treatment and time, total porosity increased by 14.29% in clay soil. The highest increase in hydraulic conductivity was observed in clay and loam soil with 6% VPC and in sandy loam soil with 6% OPC. Compost applications increased field capacity the most in sandy loam soil. The impact of compost on field capacity and porosity of soils varied according to soil texture, compost material, application amount, and time elapsed after compost application. The high BJH surface area of clay soil decreased from 15.830 m2/g to 12.977 m2/g with the addition of OPC.